The Quality of Sleep in Energy Drink Consumers and Non-Energy Drink Consumers among University Graduates - PETER, ANOOP; REDDY, K. JAYASANKARA; JAISMIN (International Journal of Psychosocial Rehabilitation, 2020)
Energy drinks are a group of beverages used by consumers to provide an extra boost in energy, promote wakefulness, provide cognitive and mood enhancement. The consumption of energy drinks has increased over the years in adults due to the effective advertising of the products’ energizing capacity. The psychoactive stimulating substance called caffeine is the main ingredient of the drinks which is an addictive substance and can cause psycho- somatic problems in the users. These Caffeinated drinks, while enhancing wakefullness reduce the sleep quality of the consumer. Thus, this study with quantitative research design explores the quality of sleep among energy drink users (ED) and non- energy drink users (NED). The sample population for both the groups were selected from college- going adults. The Pittsburg sleep quality index (PSQI) with its five dimensions, namely, sleep latency (SL), subjective sleep quality (SQ), Sleep duration (SD), habitual sleep efficiency (SE), Sleep Disturbances (SDi), use of Sleeping Medications (SM), and daytime dysfunction (DD), was employed to assess global quality of sleep. These dimensions of both groups were compared with Mann-Whitney U test. Gender-based sleep quality difference in the ED group was also analyzed. The findings showed that consumers have experienced significant effects in some of the dimensions of sleep quality. Findings of the study can aid in psychoeducation, formulation of legal regulation, and baseline data for further research.